Muslim Brothers in Egypt: politics of generational gaps - Abdelgawad, Doha Samir Mostafa (AUC Knowledge Fountain, 2012)
This thesis is an attempt to address the politics of generational gaps within Muslim Brotherhood Movement in Egypt since mid 1980s till 2011. It sheds light on patterns of generational interactions, issues of concern, and their impact on the future trajectory of the Movement. It conceptually employs the Generational Unit Model, drawn largely from the work of Karl Mannheim. In doing so, the study applies focused semi-structured interviews with the movement's affiliated members from antagonistic generational units. The study addresses the socioeconomic and political context that shape the consciousness of two generational waves within the movement. It descriptively addresses the nature of generational relationship between some of the 1970s generation, young Brothers, and the movement's leadership. It denotes reasons behind the establishment of new political organizations including The Center party (Al Wasat), The Egyptian Current Party (Al Tayar al Masry), and The Renaissance Party (Al Nahda Party). The study highlights different perceptions and schools of thought shared by Brothers towards social reality, and tools of reforming the movement and the Egyptian political system.